The Influence of Marketing Content, Online Customer Review, EWOM on the Decision to Purchase Moisturizer Products on the Tiktok Application - Della Ayu Safitri; Rafly Alfikri Sobari; May Dedu (Riviera Publishing, 2025)
This study investigates the influence of content marketing, online customer reviews, and Electronic Word of Mouth (E-WOM) on purchasing decisions for moisturizer products via TikTok, a platform increasingly pivotal in consumer behavior. Employing a quantitative approach, data were collected from 247 active TikTok users in Indonesia through online questionnaires and analyzed using SPSS Version 27 (multiple linear regression). Results revealed that online customer reviews (?=0.479) exerted the strongest influence, followed by E-WOM (?=0.359) and content marketing (?=0.159), collectively explaining 47.3% of purchasing decisions (R²=0.473). The findings underscore the critical role of peer-generated content in building trust and reducing uncertainty, while TikTok’s interactive format amplifies E-WOM’s impact. The study contributes to the Technology Acceptance Model (TAM) by validating TikTok-specific drivers of consumer behavior. Practical implications suggest businesses prioritize authentic reviews and E-WOM strategies on TikTok to enhance consumer engagement and sales. Unexplained variance (52.7%) calls for future research on influencer marketing and cross-platform comparisons.